Nutritional requirements for the improvement of growth and sporulation of several strains of Monascus purpureus on solid state cultivation - Ajdari, Zahra; Ebrahimpour, Afshin; Abdul Manan, Musaalbakri; Hamid, Muhajir; Mohamad, Rosfarizan; Ariff, Arbakariya (Hindawi Publishing Corporation, 2011)
This paper describes the nutritional requirements for the improvement of growth and sporulation of several strains of Monascus purpureus on solid state cultivation. The findings revealed that glucose enhanced growth of all M. purpureus strains tested but inhibited the sporulation rate. On the other hand, sucrose induced sporulation but inhibited production of cell mass. A combination of glucose and sucrose greatly enhanced sporulation and cell mass production of M. purpureus. Although growth and sporulation rate were related to the ratio of carbon to nitrogen (C/N ratio), the types and concentrations of carbon and nitrogen sources also greatly influenced the growth kinetics. Among the media tested, Hiroi-PDA medium was the most preferred medium for all M. purpureus strains tested for the enhancement of radial growth rate, sporulation, and cell production. Hence, Hiroi-PDA could be suggested as the generic basal medium for the cultivation of M. purpureus. However, individual medium optimization is required for significant enhancement in growth and sporulation of each strain of M. purpureus.